Frequency content in an axially impacted bar subject to boundary conditions - Rensfelt, A.; Söderström, T. (IFAC Proceedings Volumes, 2008)
We analyze the frequency contents of strain waves in an axially excited bar, where one end of the bar is subject to a free end boundary condition. The analysis is treated in the context of identification of viscoelastic materials. The free end boundary condition leads to very particular constraints on the wave propagation in the bar and it is shown how this influences the identification. Wave propagation in both elastic and viscoelastic materials is treated, and the validity of the analysis confirmed through simulated and (in the case of viscoelastic materials) experimental data. The analysis is then used in order to interpret the large frequency variations in previous studies concerning the accuracy of the estimate and optimal input signal, respectively.